Peningkatan Kemampuan Penalaran Matematika Siswa SMK Kelas X Melalui Pembelajaran dengan Pendekatan Realistic Mathematics Education (RME)(PTK Siswa Kelas X di SMK Muhammadiyah 01 Boyolali Tahun 2016/2017) - Pramusinta, Nindia, Sri Rejeki, M.Pd., M.Sc (2017)
The purpose of this research is to improve students' reasoning ability skills by applying Realistic Mathematics Education approach.. This research is a Classroom Action Research (CAR). The subject that receive the action is grade X TKR 4 of Muhammadiyah Vocational High School 01 of Boyolali. The number of students of grade X TKR 4 are 21 students. The data collection techniques are observation, field notes, test and documentation. Based on the research analysis it can be concluded that the application of Realistic Mathematics Education approach can improve the reasoning ability skills of student grade X TKR 4. It can be seen from the increase in the precentage of the indicators of reasoning ability skills, namely 1) the ability to present mathematical statement in writing in the form of a model of a prior act of from 28.57% increase to 90% 2) the ability drawing conclusion of answers to existing problem as much as 38.10% increase to 70% and 3) the ability to analyze situations mathematically using patterns and relationships from 23.81% increase to 65%. It can be concluded that by applying Realistic Mathematics Education (RME) approach can improve of students' reasoning ability skills.